Prophylactic Therapy of Silymarin (Milk Thistle) on Antituberculosis Drug-Induced Liver Injury: A Meta-Analysis of Randomized Controlled Trials - Lina Tao; Xiaoyu Qu; Yue Zhang; Yanqing Song; Si-xi Zhang (Canadian Journal of Gastroenterology and Hepatology)
Background. Prophylactic therapy with silymarin to prevent the development of antituberculosis drug-induced liver injury (anti-TB DILI) has been under debate. We aimed to evaluate the effect of silymarin in the prevention of anti-TB DILI. Methods. We searched MEDLINE, PubMed, Embase, and Cochrane Central Register of Controlled Trials (CENTRAL) up to 30th November 2018. Randomized controlled trials (RCTs) that compared silymarin and placebo to prevent anti-TB DILI were included. All statistical analyses were conducted using STATA 12.0 software. Standardized mean difference (SMD) and risk ratio (RR) with 95% confidence intervals (CIs) were used to evaluate the effect of silymarin. The quality of included studies was assessed according to Cochrane handbook. Funnel plots and Egger’s tests were carried out to evaluate publication bias. Sensitivity analysis was conducted to assess the influence of each study. Results. A total of 1198 patients from five RCTs (585 with silymarin and 613 with placebo groups) were included. Overall, silymarin significantly reduced the occurrence of anti-TB DILI at week 4 [RR: 0.33, 95% CI (0.15, 0.75)]. In addition, silymarin exerted protective effect on liver function in patients undergoing anti-TB drugs [SMD = − 0.15, 95% CI (−0.24, −0.07), P < 0.001 (ALT); SMD =−0.14, 95% CI (−0.23, −0.06), P = 0.001(AST); SMD =−0.12, 95% CI (−0.20, −0.03), P = 0.008 (ALP)]. Silymarin led to similar AEs in placebo groups [OR: 1.09, 95% CI (0.86, 1.39), P = 0.47]. Conclusion. Prophylactic therapy of silymarin is contributed to a noticeably reduced risk of development of anti-TB DILI four weeks after the initiation. In addition, silymarin significantly improved the liver function in patients who are receiving anti-TB drugs.